Interferon Gamma Inhibits Adipogenesis In Vitro and Prevents Marrow Fat Infiltration in Oophorectomized Mice1. (9th April 2012) - Vidal, Christopher; Bermeo, Sandra; Li, Wei; Huang, Dao; Kremer, Richard; Duque, Gustavo
Abstract: Interferon gamma (IFNγ) has been reported to induce osteoblastogenesis from mesenchymal stem cells (MSCs) both in vitro and in vivo. With ageing, adipocytes outnumber osteoblasts within the bone microenvironment leading to a decrease in bone formation. Since both osteoblasts and adipocytes are of mesenchymal origin, we hypothesized that IFNγ treatment might negatively affect adipogenesis while stimulating osteoblastogenesis in human MSC. To test this hypothesis, human MSCs were induced to differentiate into adipocytes in the presence or absence of osteogenic doses of IFNγ (1, 10, and 100 ng/ml). IFNγ‐treated MSC showed a decrease in adipocyte differentiation and lipid deposition when compared with vehicle‐treated controls. Additionally, adipogenic markers were significantly decreased by IFNγ treatment at the same doses that have been reported to have a strong osteogenic effect in vitro. Furthermore, DNA binding of peroxisome proliferator‐activated receptor gamma was significantly lower in IFNγ‐treated differentiating MSC. Subsequently, ovariectomized C57BL6 mice were treated with osteogenic doses of IFNγ three times a week for 6 weeks. In distal femur, treated mice showed significantly higher hematopoiesis concomitant with lower levels of fat volume/total volume, adipocyte number, and expression of adipogenic markers when compared with the vehicle‐treated mice. Together, these findings demonstrate that, at osteogenic doses, IFNγ also acts as an inhibitor of adipogenesis in vitro and prevents marrow fat infiltration while favors hematopoiesis in ovariectomized mice. STEM CELLS 2012;30:1042–1048